Effect of Exposing Layer and Broiler Eggs to Red or White Light During Incubation - Archer , Gregory S. (International Journal of Poultry Science, 2015)
Previous study has shown that layer and broiler eggs filter light. It was hypothesized that due to the difference in pigment of the eggshells that utilizing red light would improve hatch in white eggs similarly to that observed in brown eggs using white light. To determine we incubated chicken eggs (n = 2592) under either no light (dark), red light, or white light; the light level was 250 lx and equal numbers of layer and broiler eggs were used. White light was observed to increase (p = 0.05) hatch of fertile (92.5±1.3%) over dark and red light incubated broiler eggs (86.1±2.2 and 86.1±2.6%). White light had no effect on hatch of fertile when compared with dark incubated white layer eggs (68.11±12.8%); however, red light (88.0±4.8%) showed an increased (p = 0.05) hatch of fertile over dark incubated white layer eggs. Brown eggs exposed to white (0.85±0.02) or red (0.80±0.02) improved (p<0.05) the proportion of non-defect chicks over dark (0.52±0.02) incubated eggs. Similarly, white eggs show the same trend of white (0.79±0.02) or red (0.72±0.04) improved (p<0.05) the proportion of non-defect chicks over dark (0.51±0.02) incubated eggs. Chick length was not affected (p>0.05) by any treatment. These results indicate that red light is possibly the key spectrum to improving hatchability.